CAUSATIVE AGENTS OF ACUTE RESPIRATORY DISEASES IN CHILDREN (Multidisciplinary Journal of Science and Technology, 2026)
Acute respiratory diseases (ARDs) remain one of the leading causes of morbidity and mortality among children worldwide. These infections are caused by a wide range of viral, bacterial, and atypical pathogens that affect the upper and lower respiratory tract. The present study aims to analyze the main causative agents of acute respiratory diseases in children, identify their epidemiological patterns, and evaluate their clinical significance. The study is based on a review of clinical observations and laboratory-confirmed cases. The results indicate that viral pathogens, particularly respiratory syncytial virus (RSV), influenza viruses, and adenoviruses, dominate in pediatric ARDs, while bacterial infections such as Streptococcus pneumoniae and Haemophilus influenzae are associated with complications. Understanding the etiological structure of ARDs is essential for effective diagnosis, treatment, and prevention.